Presentation of Marimba, Drum Set with Concerto Repertoire for Marimba, Tanjung Katung and Lexicon - Shalsabilla, Tiara; Marh, Fahmi; Emridawati, Emridawati (Scoring: Journal of Film Music, 2024)
The Solis Marimba performance presents two compositions, namely the Concerto for Marimba and Tanjung Katung. Concerto for Marimba is a musical composition created by Kees Schoonenbeek, played with two mallet techniques in a modern classical style with piano accompaniment. Meanwhile, the second composition is a jazz version of the song Tanjung Katung played by the Geliga music group. This song was also sung by a quite well-known Malay singer in Indonesia, namely Iyeth Bustami. This song is played with the Malay style two mallet technique using combo band accompaniment. Then the Drumset soloist performed with the song Lexicon created by Isyana Sarasvati in the progressive rock genre through the Combo Band format. The performance method for Marimba and drumset soloists uses performance stages starting from preparation of the composition to be played, individual and joint practice processes, and performance. The results of this presentation show that solo marimba and drumset performances can be performed through the application of stroke techniques such as single stroke, and double stroke, all through the expression, style, and interpretation of the presenter in front of the audience.